Well-organized organosilane composites for adhesion enhancement of heterojunctions. (16th June 2020) - Liu, Tzu-Jung; Sil, Manik Chandra; Chen, Chih-Ming
Abstract: Flexible copper clad laminate (FCCL) is the key base material for versatile applications such as mobile devices, wearable electronics, and point-of-care biosensors. Development of adhesiveless FCCL is urgent to achieve a thinner, lighter, and thermally stable substrate for advanced high-frequency (5G) applications. In this study, a co-silanization method is proposed to functionalize the polyimide (PI) surface for efficient metal immobilization and adhesion enhancement. The co-silanization treatment features the establishment of a barricade-like network structure by the assistant organosilane, trimethoxyphenylsilane (TMPS), to generate spatial confinement effect (SCE) to effectively control the positioning and grafting orientation of the functional organosilane, 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane (ETAS), on the PI film. Benefitting from the effective positioning and grafting, the two types of organosilanes form a composite well-organized molecular nanolayer which is in possession of strong tethering ability for metal attachment and immobilization. Compared to the mono-silanization system with ETAS only (0.652 kgf/cm), the co-silanization treatment (ETAS + TMPS) remarkably enhances the peel strength of the deposited metal layer on PI by 53% ( 1 kgf/cm).